Thatcher’s Victims vs. Beveridge’s Sons: The New Cleavage of European Parties - Roberto Segatori (Coordinamento SIBA, 2015)
The Rokkans’ theory of cleavages has traditionally been a valid helpful instrument, although questionable, to interpret the nexus between social dynamics and party models. Thanks also to this theo-ry, during the hundred years between 1885 and 1985, European political party classification, at least where their origins are concerned, is reasonably straightforward. At the end of the sixties of ‘900, the per-formance of the political actors in terms of policy stimulated a level of feedback on the social conditions of populations to the point of reducing the impact of the traditional cleavages. The thirty-year “Golden Age” steadily led the population to believe in a world where the affirmation of universalistic social rights was an acquired right regardless of offsetting economic measures. But in the following forty years, with this con-viction still holding, the economic conditions for the sustainability of that model were overturned, and the prospect, therefore, of social benefits for all changed radically. Especially after the 2008 crisis, a new cleavage explodes with such an intensity that it actually squares the interests of the “protected” (state employees with steady jobs, workers of large and medium-sized firms protected by the Unions) with the “non-protected” (the unemployed, self-employed and seasonal labourers), in other words those of the established and non-established. In this framework, if they want to survive, the political parties both old and new, are continually being pressurised by an agitated electorate to realign themselves. And while in the short term gain votes populist and nationalist parties, the nature of the latest cleavage seems there-fore to be a challenge especially for those parties which find themselves managing the “social blocs”, gen-erated from the classic cleavages, and the identity nuclei.